Samizdat: The Literary Self-Publishing Movement in Leningrad 1950s – 1980s (ENTHYMEMA, 2015)
V. Dolinin and D. Severiukhin are authors associated with the authoritative encyclopaedia Samizdat Leningrada (2003). Both were deeply involved in Samizdat publishing in Leningrad. Dolinin was arrested in 1982 and spent four years in prison. This article is a broad survey of the origins, development and values of Leningrad unofficial culture during the ‘classical’ period (1950s-1980s) of Soviet Samizdat.
Keywords: Second culture; Samizdat; unofficial literature